Intersectional Crossroads: A Deeper Look Into Latinx Girl Gang Involvement and Affiliation - Barahona-Lopez, Kati (Journal of contemporary criminal justice, 2025)
Historically, scholars understood girl gang involvement through the lens of boy’s gang experience. Solely relying on the aforementioned demographic’s gang experience dismisses the intersectional nature of girl gang involvement. This article explores how Latinx teenage gang members describe and understand their involvement and/or affiliation with gangs by using multiracial feminism and intersectionality as theoretical frameworks. We found that multiracial feminism is valuable in explaining girl gang involvement. Intersecting identities affect how Latinx girls perceived their gang participation and navigated through formal and informal institutions and social interactions with fellow gang members.